Paid Parking Performance at Depok Lama Station - Pratama, Fariz Asmi; Syaiful, Syaiful; Aminda, Renea Shinta (ASTONJADRO, 2023)
PT Kereta Api Indonesia (Persero) or PT KAI is a State-Owned Enterprise (BUMN) that provides rail transportation services, the old Depok station is one of PT KAI's operating facilities which stops regularly to get on and off passengers, Depok Lama Station is in the area operational area one located in Pancoran Mas District, Depok city. The increase in passengers at the Old Depok Station and the inability to accommodate parking facilities at the Old Depok Station. Some passengers choose to park their vehicles in private parking lots. Therefore, according to the author, it is necessary to evaluate the performance of the current parking area as a future plan. So that it can provide an alternative solution for parking lots at the Old Depok Station, and also overcome so that train passengers don't get a parking space anymore. It also aims to provide comfort for train passengers. This research was conducted to evaluate the parking area at Depok Lama Station. This evaluation is an important step that must be carried out, in order to identify problems that occur in the parking system at Depok Lama Station. This data collection uses a quantitative method with direct observation in the field at the old Depok station, while the literature is used as a reference for secondary data. Based on the survey results and data analysis that the author obtained for 10 days, namely the existing condition of the parking lot obtained secondary data using the survey method so as to produce existing data on a 230m2 motorbike parking area with a capacity of 100 SRP (Parking Space Unit) and a slope angle of 90° at the station old depot. In this analytical study, the results of the largest accumulated stasis capacity were 143 vehicles with an average parking duration of 08:14 hours on Thursday, 01 June 2023. During the ten days of the survey it was found that the maximum parking volume was 150 vehicles with an accumulation of vehicle parking a maximum of 150 vehicles that occurred on June 1, 2023, the highest turnover of motorcycle parking at Depok Lama Station reached 150.00%, this indicates that the performance of motorcycle parking is quite high. The capacity of motorbike parking space at the old Depok station can meet the existing parking needs. This is shown by looking at the parking index exceeding 100%.